2019
DOI: 10.3389/fphys.2019.00381
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Disease Subjects Have a Distinct Abnormal Autonomic Phenotype Characterized by Peripheral Vasoconstriction With Blunted Cardiac Response to Head-Up Tilt

Abstract: In sickle cell disease (SCD), prolonged capillary transit times, resulting from reduced peripheral blood flow, increase the likelihood of rigid red cells entrapment in the microvasculature, predisposing to vaso-occlusive crisis. Since changes in peripheral flow are mediated by the autonomic nervous system (ANS), we tested the hypothesis that the cardiac and peripheral vascular responses to head-up tilt (HUT) are abnormal in SCD. Heart rate, respiration, non-invasive continuous blood pressure and finger photopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
2
17
1
Order By: Relevance
“…In the few subjects who had a repeat study, these vasoreactivity trends were reproducible. In fact, an autonomic vasoconstriction reactivity signature that is inherent to the individual appears to be present, as further evidenced in our experiments with autonomic tilt table testing [55].…”
Section: Autonomic Dysfunction and Peripheral Vasoreactivity In Scdsupporting
confidence: 55%
See 1 more Smart Citation
“…In the few subjects who had a repeat study, these vasoreactivity trends were reproducible. In fact, an autonomic vasoconstriction reactivity signature that is inherent to the individual appears to be present, as further evidenced in our experiments with autonomic tilt table testing [55].…”
Section: Autonomic Dysfunction and Peripheral Vasoreactivity In Scdsupporting
confidence: 55%
“…Thus, the blood pressure normalizes due to the adaptive autonomic responses. Out of the 66 subjects (27 SCD, 13 anemic and 26 non-anemic controls) who were subjected to HUT testing, only 30% of SCD subjects had a normal response (tachycardia + vasoconstriction; Figure 5) [55]. All subjects, except for one, who responded with only peripheral vasoconstriction had SCD.…”
Section: Autonomic Dysfunction and Peripheral Vasoreactivity In Scdmentioning
confidence: 99%
“…Consistent with this finding, Willen et al 16 showed no significant association between low mean nocturnal SpO 2 and incidence of VOC in the SAC participants studied here. On the other hand, we 5,7,8,24,25 and others 26‐29 have shown significant dysautonomia in SCD. Therefore, we examined measures of cardiac ANS balance (LHR, RMSSD) but found no association with VOC rate (modesl 8‐9 Table S2).…”
Section: Discussionmentioning
confidence: 62%
“…Of note, impaired CA (226–228) and reduced CVR (229, 230), have also been observed following sympathetic stimulation in animals and humans. There is evidence for autonomic nervous system dysfunction in SCD, with enhanced sympathetically mediated vasoconstriction reflexes (218, 231–234), which theoretically, could compound any effect of reduced NO. Although there are no data comparing CVR, CA, and the interaction between them in SCD, a vulnerability in the availability of regulatory agents, either alone or in combination with autonomic nervous system dysfunction, may mean that normal CVR and CA ranges are right-shifted and/or narrower with loss of the plateau.…”
Section: Hemodynamic Compromisementioning
confidence: 99%